2003
DOI: 10.1517/14728214.8.2.489
|View full text |Cite
|
Sign up to set email alerts
|

Cancer vaccines entering Phase III clinical trials

Abstract: The last 10 years have seen a growth in the number of tumour antigens identified from immune responses raised in patients. The discovery that tumours can be recognised by the immune system stimulated a great deal of work characterising the molecular mechanisms underlying immune recognition. This in turn has led to an impressive array of immunological approaches to the generation of cancer vaccines; these range from molecularly defined T cell epitopes, antibody-based vaccines, cytokine therapies, immune modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Whole cell vaccines, perhaps the oldest approach, utilize irradiated cancer cells, either autologous or allogeneic, as source of tumor antigens either in combination with adjuvants, or genetically modified [12]. They have been shown to induce tumor-specific immunity and durable anti-tumor responses in a number of Phase I and II trials [13]. However, in the past few years several high-profile Phase III trials, including those conducted using the promising GVAX technology (see below) have failed to meet the predefined endpoints [14].…”
Section: Non Genetic Vaccinesmentioning
confidence: 99%
“…Whole cell vaccines, perhaps the oldest approach, utilize irradiated cancer cells, either autologous or allogeneic, as source of tumor antigens either in combination with adjuvants, or genetically modified [12]. They have been shown to induce tumor-specific immunity and durable anti-tumor responses in a number of Phase I and II trials [13]. However, in the past few years several high-profile Phase III trials, including those conducted using the promising GVAX technology (see below) have failed to meet the predefined endpoints [14].…”
Section: Non Genetic Vaccinesmentioning
confidence: 99%
“…[19][20][21][22][23] Dendritic cell-based preparations are already in clinical trials against cancer. 24,25 The preclinical results of DC-based vaccines in animal models of fungal infection have been reviewed elsewhere. 26,27 Earlier, it was demonstrated that DCs are activated after interacting with fungal pathogens, such as Aspergillus conidia, 28 Candida yeasts, 29 and coccidioidal ligands, such as T27K antigen.…”
Section: Dendritic Cells Are a Potent Adjuvant And Play An Important mentioning
confidence: 99%
“…Indeed, mAbs have shown great promises for the treatment of cancer and several are now available to the market [68]. Although none of them are directed to carbohydrate structures so far, some clinical and preclinical studies with mAbs against gangliosides are very encouraging for a further development in humans [69,70].…”
Section: -Tacas As Tools For Diagnosis and Immunotherapymentioning
confidence: 99%